The relationship between landscape heterogeneity and ecosystem services in Santa María Huatulco, Oaxaca, Mexico - Alfonso Martínez, Ángel A. (2024)
[Introduction]: The variability of geographic space, in terms of the horizontal structure of landscapes, influences ecology and suggests an association between landscape heterogeneity indices (LHI) and ecosystem services (ES). This relationship is crucial for conservation and sustainable development in Latin America, given the diversity of landscapes, from tropical forests to snow-capped mountains and deserts, which harbor a unique wealth of biodiversity and ecological functions. [Objective]: The objective of this study was to determine the relationship between LHI and ES. [Methodology]: Fourteen landscape heterogeneity indices and seven ecosystem services were calculated in Santa María Huatulco, Oaxaca, and related to the estimated ecosystem services for the same area. [Results]: The models showed a statistically significant relationship between LHI and ES, suggesting that certain LHI can influence the provision and distribution of ES. [Conclusions]: Therefore, understanding how LHI affect ES is essential to promote sustainable development in Latin America.